Occupational stress of elementary school teachers after eased COVID-19 restrictions: a qualitative study from China - Yao, Yujing; Xu, Jie (Frontiers in Psychology, 2023)
Background On December 7, 2022, China optimized its virus response and significantly shifted its epidemic policy by downgrading COVID management and gradually restoring offline teaching in schools. This shift has brought many impacts on teachers. Aims Through qualitative research of thematic analysis, this paper studies the occupational pressure of primary school teachers in China after the shift in epidemic policy. Methods Two recruitment methods are adopted for this study. One was to email the principals of several primary schools in Zhejiang Province to introduce the research project and indicate the idea of recruiting participants. With their help, we have found teachers who volunteer to participate. The second was to release recruitment information in the network forum (e.g., online teacher forums) to find volunteer participants. Through semi-structured interviews and diaries, 18 primary school teachers from different regions and schools in Zhejiang Province were interviewed. All responses in the interviews were transcribed anonymously. Braun and Clarke’s thematic analysis was used to analyze the participants’ responses. Results Eighteen participants took part in the research project. Forty-five final codes, generated from 89 codes initially obtained from the dataset, are classified into five final themes: uncertainty, overburdened, neglected, worry about students, and influence, which reflect the professional stress of primary school teachers following the epidemic prevention policies relaxed. Conclusion Five themes were identified in the research. The problems described by the participants include burdensome offline activities, being disturbed out of hours, and appearing understaffed for the infection. These problems harmed the participants’ mental health, including anxiety, fatigue, stress, and other adverse psychological conditions. Awareness and attention to the psychological situation of primary school teachers after the eased COVID control are crucial. We believe protecting teachers’ mental health is necessary, especially in this particular period.